Lua you xi AI kai fa zhi nan = Learning game AI programming with Lua / = Learning game AI programming with Lua - Young, David (Ren min you dian chu ban she = Posts & Telecom Press, 2017)
Detailed summary in vernacular field only.
880-05;Ben shu you Yingguo Packt Publishing gong si shou quan Ren min you dian chu ban she chu ban
Keywords: Lua (Computer program language); Artificial intelligence -- Computer programs; Video games -- Programming; Video games -- Design; Application software -- Development; Lua (Langage de programmation); Intelligence artificielle; Logiciels; Jeux vidéo; Programmation; Jeux vidéo; Conception; Logiciels d'application; Développement